2018
DOI: 10.1128/jcm.01369-17
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Evaluation of the Modified Carbapenem Inactivation Method and the Carba NP for Detection of Carbapenemase-Producing Pseudomonas aeruginosa and Acinetobacter baumannii

Abstract: The purpose of this study was to develop the modified carbapenem inactivation method (mCIM) for the detection of carbapenemase-producing (CP-PA) and carbapenemase-producing (CP-AB) and perform a multicenter evaluation of the mCIM and Carba NP tests for these nonfermenters. Thirty and 30 isolates previously characterized by whole-genome sequencing from the CDC-FDA Antibiotic Resistance Isolate Bank were evaluated, including CP isolates (Ambler class A, B, and D), non-carbapenemase-producing (non-CP) carbapenem-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 13 publications
7
37
0
Order By: Relevance
“…The CNP test is based on the in vitro hydrolysis of imipenem and has been extensively evaluated for detecting carbapenemases in Enterobacteriaceae (140) and Pseudomonas (151). The test has both excellent specificity (84% to 100%) and sensitivity (93.3% to 100%) for detecting carbapenemases, including NDM in Enterobacteriaceae (152)(153)(154) and P. aeruginosa (155). However, CNP is relatively labor-intensive, as reagents need to be prepared in-house, and some have short shelf lives (e.g., 72 h) (156).…”
Section: Detection Of Carbapenemase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The CNP test is based on the in vitro hydrolysis of imipenem and has been extensively evaluated for detecting carbapenemases in Enterobacteriaceae (140) and Pseudomonas (151). The test has both excellent specificity (84% to 100%) and sensitivity (93.3% to 100%) for detecting carbapenemases, including NDM in Enterobacteriaceae (152)(153)(154) and P. aeruginosa (155). However, CNP is relatively labor-intensive, as reagents need to be prepared in-house, and some have short shelf lives (e.g., 72 h) (156).…”
Section: Detection Of Carbapenemase Activitymentioning
confidence: 99%
“…A multisite evaluation found that the mCIM is accurate for detection of carbapenemases in P. aeruginosa, with 86.7% to 100% sensitivity and 93.3% to 100% specificity. Detection of carbapenemase-producing Acinetobacter with this method is more problematic, with 36.3% to 95.7% sensitivity and 28.6% to 100% specificity (155). Another study has shown mCIM to have low sensitivity (45.1%) for the detection of carbapenemases in Acinetobacter and Pseudomonas (174).…”
Section: Detection Of Carbapenemase Activitymentioning
confidence: 99%
“…Given that 15-33% of P. aeruginosa isolates are multidrug resistant (have at least one resistance mechanism) [16,17] and that resistance is associated with up to fivefold greater mortality [18,19], choosing the right antibiotic combinations have a tremendous impact on patient outcomes. Advances in the rapid diagnosis of P. aeruginosa, and use of both rapid phenotypic tests such as CARBA NP [20] or rapid molecular diagnostics to identify specific ESBL and carbapenemase enzymes, have enhanced the clinician's ability to get patients on the right therapy sooner. Identification of patient risk factors, including prior antibiotic exposure, and knowledge of local trends in resistance patterns are useful in selection of empiric antibiotics, until antimicrobial susceptibilities and genotypic results are available for guidance.…”
Section: Current Therapeutic Strategies To Treat Infections With Resimentioning
confidence: 99%
“…He has studied the emergence and spread of antibiotic-resistant organisms (9)(10)(11)(12)(13)(14) as well as the methods for and utility of detecting such organisms in the microbiota (15)(16)(17)(18). Dr. Jenkins has published on methods of susceptibility testing throughout his career, most recently on detection of carbapenem resistance in Gram-negative bacilli (19)(20)(21). His interest in rapid diagnostic testing has been driven by a desire to improve patient care by providing timely results, with his research including studies of molecular and phenotypic tests to detect the spread of clonal organisms in the hospital setting, resistant organisms, and respiratory virus infections (22)(23)(24)(25)(26).…”
mentioning
confidence: 99%